Assessment of family functioning: evaluation of the General Functioning Scale in a Swedish Bariatric Sample. Issue 3 (9th November 2015) - Bylund, Ami; Årestedt, Kristofer; Benzein, Eva; Thorell, Anders; Persson, Carina
Abstract : Background: The General Functioning Scale (GFS) was developed to assess self‐perceived overall family functioning. The scale has satisfactory psychometric properties, is internationally recognised and has been used in different contexts. However, no validated Swedish version is available. Healthy family functioning can support patients and help them adhere to treatment regimens. Moreover, it maintains the physical and emotional health and that of the family as a unit. Yet, there is limited information regarding family functioning postgastric bypass surgery. Thus, it is important to use validated instruments to understand family functioning in bariatric contexts. Aim: To evaluate aspects of reliability and validity in GFS in a Swedish bariatric sample, focusing on factor structure. Method: The Swedish version of the GFS (S‐GFS) was administered on two occasions to 163 participants who had undergone gastric bypass surgery 6–8 weeks prior to testing. Internal consistency, temporal stability and construct validity were assessed. Results: Data were positively skewed. The S‐GFS showed good internal consistency (ordinal α = 0.92) with a sufficient overall mean interitem correlation (0.500) and adequate temporal stability (intraclass correlation coefficient = 0.833). After modifying response alternatives, confirmatory factor analysis indicated acceptable fit for a one‐factor model. Conclusion: The scale is a promising tool for assessing family functioning in bariatric settings. The S‐GFS showed satisfactory reliability – consistent with prior research – and acceptable validity in the study sample. This study contributes to the limited research on the scale's validity. However, the S‐GFS needs to be evaluated in different cultural and clinical contexts, focusing on various aspects of validity and responsiveness (sensitivity to detect significant change over time) in different samples.